Differences in Financial Behavior of MSME Vendors Before and After the Establishment of Teras Malioboro - M. Chambali Darma PUTRA; Hendrato Setiabudi NUGROHO (International Journal of Environmental, Sustainability, and Social Science, 2025)
The relocation of street vendors (PKL) to Teras Malioboro is a Yogyakarta City Government policy aimed at developing the Malioboro area as a leading tourist destination. This policy has created new dynamics in the economic activities of MSME vendors. The change in trading location is suspected to have led to changes in the financial behavior, financial attitudes, financial well-being, and use of financial technology among MSME vendors in Malioboro for the sustainability of their businesses. This study aims to determine whether there are differences in financial behavior, financial attitudes, financial well-being, and use of financial technology among MSME vendors before and after the establishment of Teras Malioboro. This study is a comparative study with a quantitative approach, using primary data obtained through questionnaires from 90 relocated MSME vendors in Teras Malioboro 1. Data analysis was conducted using a paired-sample t-test. This study revealed significant differences in the financial behavior, financial attitudes, financial well-being, and use of financial technology among MSME vendors in Malioboro before and after the establishment of Teras Malioboro. The relocation of MSME traders in Malioboro resulted in significant negative changes in their financial behavior, attitudes, and well-being. Conversely, MSME traders' use of financial technology experienced positive changes after the relocation.